Pengembangan Media Pembelajaran Alat Ukur Panjang Mikrometer Sekrup dan Jangka Sorong untuk Siswa SMA dengan Perangkat Lunak Construct 2 (UPEJ Unnes Physics Education Journal, 2017)
Measurements with using micrometer and vernier caliper is one of the subject taught in high school level. The problem faced is the small size of the tool making it difficult for students when the teacher demonstrates the tools. The solution to solve this problem is by develop a learning media with the use of Construct 2 software. The development of this media follows the 4D model which consists of 4 stages of development that is defining, designing, developing, and disseminating. Validation test by experts and feasibility questionnaires by users of teachers and students have been done to determine the feasibility of the learning media. Aspects assessed by the expert is the aspect of media feasibility in terms of visual communication design, software engineering aspects and aspect in term of learning contents. The media feasibility test by users is done in SMA Muhammadiyah 2 Magelang and SMAN 1 Pecangaan Jepara. The data obtained show that the media created have very good categories in terms of visual communication design and learning contens, as well as good categories in terms of software engineering aspects. The media created are also rated very well by students and teachers.